Prussian blue nanoparticles–mediated sensing and removal of 137Cs - Pandey, Prem C.; Yadav, Hari Prakash; Tiwari, Atul Kumar; Sawant, Shilpa N.; Sinharoy, Prithwish; Banerjee, Dayamoy; Narayan, Roger J. (Frontiers in Environmental Science, 2023)
Prussian blue nanoparticles (PBNPs) with controlled nano-geometry were synthesized from a single precursor (potassium hexacyanoferrate) in the presence of three different reagents, namely, polyethylenimine (PEI), tetrahydrofuran (THF)/H2O2, and 2-(3,4-epoxycyclohexyl)-ethyl-trimethoxysilane (EETMS)/cyclohexanone, which enabled the controlled nucleation and stabilization of PBNPs of variable plasmonic activities for selective sensing and removal of cesium radionuclides. The results of this study show the sensing and removal of cesium ions based on the nano-geometry, magnetic behavior, and fluorescence quenching ability of PBNPs as a function of the cesium ion concentration for the first time. A similar process was used to synthetically incorporate PBNPs in mesoporous silica with potential use for the selective adsorption of 137Cs, followed by the detection of radioactivity. The distribution coefficient (Kd) for adsorption of the cesium nuclide 137Cs was calculated to be 3.2 × 104 mL/g−1, displaying both Langmuir and Freundlich adsorption isotherms. The plasmonic activity of PBNPs has enabled fluorometric sensing of cesium ions; regulating the spatial control between the functional PBNPs and fluorescence probe molecules is a promising approach for PBNP-enhanced fluorescence and fluorescence resonance energy transfer–based cesium ion sensing. Similarly, PBNPs display superparamagnetic behavior; these magnetic properties were observed to be linearly dependent on the cesium ion concentration.